2014
DOI: 10.1016/j.rmed.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Asthma Control Test in pregnant asthmatic women

Abstract: The ACT proved to be reliable and could discriminate between levels of asthma control in pregnant women confirming its value as a useful tool for the management of asthma during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Previous studies also described that ACT scores were responsive to changes in asthma course, although the report from pregnant women was based on only 10 individuals. 14,18 Furthermore, the current study provided some evidence supporting construct validity of the p-ACT as lower p-ACT scores were associated with previous exacerbations at most of the assessments. The predictive validity of the p-ACT for exacerbations before the subsequent interview was poor, regardless of the time window examined.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies also described that ACT scores were responsive to changes in asthma course, although the report from pregnant women was based on only 10 individuals. 14,18 Furthermore, the current study provided some evidence supporting construct validity of the p-ACT as lower p-ACT scores were associated with previous exacerbations at most of the assessments. The predictive validity of the p-ACT for exacerbations before the subsequent interview was poor, regardless of the time window examined.…”
Section: Discussionsupporting
confidence: 60%
“…A validation study of the ACT in pregnant women with asthma was conducted recently in Brazil using the Portuguese version of the ACT. 18 This study demonstrated that the ACT, administered through in-person interview to 40 pregnant women, discriminated between controlled and uncontrolled asthma and was responsive to symptom improvements during pregnancy. However, it is critical to confirm the validity of the ACT for pregnant women in different and larger study populations.…”
Section: Introductionmentioning
confidence: 73%
“…The positive and negative likelihood ratios were 3.052 and 0.067, respectively. The questionnaire was found to be highly effective for discriminating between controlled and uncontrolled asthma, with an area under the receiver operating characteristic (ROC) curve of 0.846 (95% CI: 0.74-0.92) [11].…”
Section: Clinical Factorsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to evaluate the association between clinical asthma control by the Asthma Control Test (ACT) in pregnancy and the Global Initiative for Asthma (GINA) classification and to compare an objective instrument for measuring pulmonary function -spirometrywith two subjective instruments for the clinical evaluation of asthma during late second trimester pregnancy [11,12]. In this study, there was a statistically significant association between the clinical control of asthma during pregnancy by the GINA classification and the ACT, with p < 0.001.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation